Water and climate security: the human impact of disrupted systems - International Water Management Institute (International Water Management Institute, 2022)
Rapid climate change is causing weather extremes in every region of the world. The global water cycle is now experiencing a structural change not seen since the last Ice Age, leaving human systems struggling to adapt and respond. Some events will have noticeable consequences in the short term, such as increased flooding from changing precipitation patterns. Others will be more long term, such as the desertification of cropland. All will have major implications for future human security. We can view climate security as climatic stressors that amplify existing risks in society and influence the security of humans, ecosystems, economies, infrastructure and societies. In that sense, climate security is directly connected to water security defined as the ability of a population to safeguard sustainable access to adequate quantities of acceptable quality water.